2021
DOI: 10.48550/arxiv.2109.13199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Faster and More Reliable Quantum SWAPs via Native Gates

Abstract: Due to the sparse connectivity of superconducting quantum computers, qubit communication via SWAP gates accounts for the vast majority of overhead in quantum programs. We introduce a method for improving the speed and reliability of SWAPs at the level of the superconducting hardware's native gateset. Our method relies on four techniques: 1) SWAP Orientation, 2) Cross-Gate Pulse Cancellation, 3) Commutation through Cross-Resonance, and 4) Cross-Resonance Polarity. Importantly, our Optimized SWAP is bootstrapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Due to the limited connection topologies of NISQ superconducting QCs of square lattice and heavy hex, SWAP gates are required to move data into qubits in the same neighborhood. It has been shown that these gates can dominate transpiled gate counts [40], [41].…”
Section: B Gate Score Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limited connection topologies of NISQ superconducting QCs of square lattice and heavy hex, SWAP gates are required to move data into qubits in the same neighborhood. It has been shown that these gates can dominate transpiled gate counts [40], [41].…”
Section: B Gate Score Methodologymentioning
confidence: 99%
“…We utilize a circuit fidelity model that captures the primary source of error as decoherence in time following the methodology of prior work [40], [41]. The fidelity of a final qubit state, F Q , over a single path or wire in the circuit exponentially decays as a function of the ratio of circuit duration time and the qubit's T 1 (relaxation rate).…”
Section: B Simulated Fidelity Improvementsmentioning
confidence: 99%
“…We can instead implement the CR gate as a negative half-CR followed by a positive half-CR gate. This polarity switch [17,18] introduces a side effect that appends two Rx(180) gates to the left and the right of the CR native gate. We can also combine the polarity switch and the gate inverse.…”
Section: Cnot Gate Variantsmentioning
confidence: 99%
“…Experimental QOC papers incur significant pre-execution calibration overhead to address this issue. By contrast, this work [48], [49] proposes a technique that is bootstrapped purely from daily calibrations that are already performed for the standard set of basis gates. The resulting pulses are used to create an augmented basis gate set.…”
Section: B Partial Compilation Of Variational Algorithms For Noisy In...mentioning
confidence: 99%